Caddyshack [videorecording (DVD)] - Ramis, Harold; Doyle-Murray, Brian; Kenney, Douglas C.; Chase, Chevy; Dangerfield, Rodney, 1921-2004; Murray, Bill, 1950 September 21-; Knight, Ted; Salmi, Albert; O'Keefe, Michael, 1955- (Disbributed by Warner Home Video, 2010)
Greenskeeper Carl Spackler is about to start World War III, against a gopher. Pompous Judge Smalls plays to win but his nubile niece Lacey Underall wants to score her own way. Playboy Ty Webb shoots perfect golf by becoming the ball. And country club loudmouth Al Czervik just doubled a $20,000 bet on a 10-foot putt. Insanity? No. Caddyshack.